2007
DOI: 10.1016/j.pain.2006.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Exploring joint effects of genes and the clinical efficacy of morphine for cancer pain: OPRM1 and COMT gene

Abstract: Pain is a complex human trait. It is likely that the interaction of multiple genes, each with a small individual effect, along with the effect of environmental factors, influences the clinical efficacy of opioids rather than a single gene alone. Polymorphisms in genes coding for the mu-opioid receptor (A118G) and catechol-O-methyl transferase (Val158Met) may be important modulators of opioid efficacy. We assessed joint effects of the OPRM1 and COMT genes in predicting morphine dose for cancer pain relief. We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
195
1
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(211 citation statements)
references
References 49 publications
11
195
1
4
Order By: Relevance
“…Regarding the COMT genotype as it relates to cancer pain, individuals with a A/A (Met/Met) genotype had a lower regional opioid signal response to pain and a higher sensitivity to pain, compared with heterozygous individuals (24). On the other hand, several clinical studies have demonstrated that the required dose of morphine was lower in subjects with an A/A genotype of COMT, compared with others (25)(26)(27). These results are consistent with our result.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the COMT genotype as it relates to cancer pain, individuals with a A/A (Met/Met) genotype had a lower regional opioid signal response to pain and a higher sensitivity to pain, compared with heterozygous individuals (24). On the other hand, several clinical studies have demonstrated that the required dose of morphine was lower in subjects with an A/A genotype of COMT, compared with others (25)(26)(27). These results are consistent with our result.…”
Section: Discussionsupporting
confidence: 91%
“…Individuals genotyped with MET158MET (rs4680) had higher MOR protein expression and lower met-enkephalin concentrations (54 ). In line with these findings, MET158MET-genotyped patients required less opioid for cancer pain (55)(56)(57)(58) and postoperative pain (59 -62 ) or showed fewer side effects (63 ). In line with this protective effect of the rs4680 polymorphism, preterm infants with the MET158 allele sooner reached a pain-free state after remifentanil or morphine premedication for endotracheal intubation (64 ).…”
Section: Comtmentioning
confidence: 66%
“…For the ABCB1 gene, we genotyped three SNPs associated with a variation (decrease or increase) of the efflux activity for many drugs: rs1128503 (C1236T) on exon 12, rs2032582 (G2677T) on exon 21 and rs1045642 (C3435T) on exon 26 [15]. Interestingly, the mutant T nucleotide for rs1045642 has been associated with a better morphine pain relief in two independent studies [16,17]. By taking these three SNPs together, some authors have defined the three main ABCB1 haplotypes [6,7]: (i) the *1 allele (C/G/C) which is the wild-type allele, (ii) the *2 allele (T/T/T), and (iii) the *2Kr allele (C/G/T).…”
mentioning
confidence: 99%